Przeszłość w nazwach własnych zapisana (na podstawie Pamiętnika Andrzeja Urbana) - Oronowicz-Kida, Ewa (Wydawnictwo Uniwersytetu Rzeszowskiego, 2017)
The material basis of the paper consists of proper names excerpted from the Memoir written at the beginning of the 20th century by Andrzej Urban, a peasant from Lutcza, Podkarpacie Region. Semantic, structural and functional analysis of the collected anthroponyms, zoonyms, toponyms and chrematonyms let us conclude that fulfilling mostly informative and locative functions, they make it possible to characterise selected aspects of rural life as it was a hundred years ago. This is life of the people who are curious of the world, who are patriotic, who respect family bonds, yield to social differentiation, take care of the nature.